Natural hydrogen seeps or salt lakes: how to make a difference? Grass Patch example, Western Australia - Aimar, Léo; Frery, Emanuelle; Strand, Julian; Heath, Charles; Khan, Shahbaz; Moretti, Isabelle; Ong, Cindy (Frontiers in Earth Science, 2023)
Natural hydrogen exploration is picking up around the world while the geogenic hydrogen system is still a frontier science. Natural hydrogen seepage can occur in the form of a sub-circular surface feature named by some authors "fairy circles". Numerous hydrogen seep-alike surface features are visible from the sky in Australia but can be difficult to distinguish from the ma ny salt lakes. In this study, we combined literature review, remote sensing, field and lab measurements (soil gas sampling, X-Ray diffraction, salinity) to uncover a potential hydrogen system and its differences with the salt lakes in the Grass Patch area in Western Australia. The local geology shows a good potential to generate hydrogen. Study of the surface geology and DEM showed that salt lakes are static old features influenced by the soil composition and long-term climatic trend whereas potential hydrogen seeps have recently appeared. This study soil-gas sampling method includes a monitoring procedure compatible with time series measurements via a portable gas analyser, getting rid of artificially produced hydrogen. Low hydrogen values (<30 ppm) have been measured. Those measurements are lower than measurements published along potential hydrogen seeps in Australia. Vegetation indexes are also less constructed than explored fairy circles in Namibia. Salinity and mineralogical results did not indicate any trend with the hydrogen but are coherent with what is found in salt lakes. A microbial system could be the source of the hydrogen but would also be linked to the soil behaviour, climatic parameters, and agricultural practices. This study underlines the need to monitor surface features over few weeks to better understand the evolution of the gas mix seeping above a structure and determine if the periodicity and variability of the leakage can be correlated with bacterial activity or a geogenic hydrogen source.